Adaptive response to a future life challenge: consequences of early-life environmental complexity in dual-purpose chicks. (28th October 2020) - Yan, Chao; Hartcher, Kate; Liu, Wen; Xiao, Jinlong; Xiang, Hai; Wang, Jikun; Liu, Hao; Zhang, Hui; Liu, Jian; Chen, Siyu; Zhao, Xingbo
Abstract: Conditions in early life play profound and long-lasting effects on the welfare and adaptability to stress of chickens. This study aimed to explore the hypothesis that the provision of environmental complexity in early life improves birds' adaptive plasticity and ability to cope with a challenge later in life. It also tried to investigate the effect of the gut-brain axis by measuring behavior, stress hormone, gene expression, and gut microbiota. One-day-old chicks were split into 3 groups: (1) a barren environment (without enrichment items) group (BG, n = 40), (2) a litter materials group (LG, n = 40), and (3) a perches with litter materials group (PLG, n = 40). Then, enrichment items were removed and simulated as an environmental challenge at 31 to 53 d of age. Birds were subjected to a predator test at 42 d of age. In the environmental challenge, when compared with LG, PLG birds were characterized by decreased fearfulness, lower plasma corticosterone, improved gut microbial functions, lower relative mRNA expression of GR, and elevated mRNA expressions of stress-related genes CRH, BDNF, and NR2A in the hypothalamus (all P < 0.05). Unexpectedly, the opposite was true for the LG birds when compared with the BG ( P < 0.05). Decreased plasma corticosterone and fearfulness were accompanied by altered hypothalamic gene mRNA expressions of BDNF, NR2A, GR, and CRH through the HPA axis in response to altered gut microbial compositions and functions. The findings suggest that gut microbiota may integrate fearfulness, plasma corticosterone, and gene expression in the hypothalamus to provide an insight into the gut-brain axis in chicks. In conclusion, having access to both perches and litter materials in early life allowed birds to cope better with a future challenge. Birds in perches and litter materials environment may have optimal development and adaptive plasticity through the gut-brain axis.